Analyzing the protease web in skin: meprin metalloproteases are activated specifically by KLK4, 5 and 8 vice versa leading to processing of proKLK7 thereby triggering its activation - Ohler, Anke; Debela, Mekdes; Wagner, Susanne; Magdolen, Viktor; Becker-Pauly, Christoph (Biological chemistry, 2010)
The metalloproteases meprin alpha and beta are expressed in several tissues, leukocytes, and cancer cells. In skin, meprins are located in separate layers of human epidermis indicating distinct physiological functions, supported by effects on cultured keratinocytes. Meprin beta induces a dramatic change in cell morphology and a significant reduction in cell number, whereas in vitro evidence suggests a role for meprin alpha in basal keratinocyte proliferation. Meprins are secreted as zymogens that are activated by tryptic proteolytical processing. Here, we identify human kallikrein-related peptidases (KLKs) 4, 5, and 8 to be specific activators of meprins. KLK5 is capable of activating both metalloproteases. Interestingly, KLK4 and 8 cleave off the propeptide of meprin beta only, whereas in contrast plasmin exclusively transforms meprin alpha to its mature form. Moreover, we show that proKLK7 is processed by meprins. N-terminal sequencing revealed cleavage by meprin beta two amino acids N-terminal to mature KLK7. Interestingly, this triggering led to an accelerated activation of the serine protease in the presence of trypsin, but not of other tryptic KLKs, such as KLK2, 4, 5, 8, or 11. In summary, we demonstrate a specific interaction between meprin metalloproteases and kallikrein-related peptidases, revealing possible interactions within the proteolytic web.